2021
DOI: 10.5624/isd.20200182
|View full text |Cite
|
Sign up to set email alerts
|

Impact of viewing conditions on the performance assessment of different computer monitors used for dental diagnostics

Abstract: Purpose This study aimed to assess the computer monitors used for analysis and interpretation of digital radiographs within the clinics of the Oral Health Centre of Western Australia. Materials and Methods In total, 135 computer monitors (3 brands, 6 models) were assessed by analysing the same radiographic image of a combined 13-step aluminium step wedge and the Artinis CDDent 1.0® (Artinis Medical Systems B.V.®, Elst, the Netherlands) test object. The number of steps a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 28 publications
(61 reference statements)
0
0
0
Order By: Relevance
“…This could reflect that the radiologists had a higher diagnostic confidence with the higher quality images on the 12 MP monitors or could possibly reflect that the images displayed on the 12 MP monitors required less windowing/leveling to make the diagnosis. Prior studies have demonstrated that larger and higher definition monitors can increase observer performance and perceived image quality for various types of tasks; [14][15][16][17][18] however, other studies did not show a significant difference. 11,19 The average decrease in TAT was <7s for each of the evaluated study types.…”
Section: Discussionmentioning
confidence: 91%
“…This could reflect that the radiologists had a higher diagnostic confidence with the higher quality images on the 12 MP monitors or could possibly reflect that the images displayed on the 12 MP monitors required less windowing/leveling to make the diagnosis. Prior studies have demonstrated that larger and higher definition monitors can increase observer performance and perceived image quality for various types of tasks; [14][15][16][17][18] however, other studies did not show a significant difference. 11,19 The average decrease in TAT was <7s for each of the evaluated study types.…”
Section: Discussionmentioning
confidence: 91%